2014
DOI: 10.1097/pai.0b013e31828e7104
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Proto-Oncogene cFMS Protein in Lung, Breast, and Ovarian Cancers

Abstract: We performed immunohistochemistry for macrophage colony-stimulating factor 1 receptor (also known as c-fms proto-oncogene product) on tissue microarrays of human nontumor lung, pulmonary squamous cell carcinomas (SCC) and adenocarcinomas (ADC), and breast and ovarian carcinomas using a commercially available anti-cFMS antibody. The specificity of the antibody was validated by Western blot and mass spectrometry analysis. Staining of cFMS was restricted to stromal fibroblasts in pulmonary SCC and ADC specimens a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“… 47 G-CSF was identified as a macrophage regulator to promote proliferation, differentiation, and survival. 48 However, G-CSF along with GM-CSF can also act as proto-oncogenes, in which they are highly expressed in various tumors 49 - 51 and also frequently found in invasive breast cancer cells. 52 They were also found in abundance in the cytokine profile of metastatic 4T1 tumors.…”
Section: Discussionmentioning
confidence: 99%
“… 47 G-CSF was identified as a macrophage regulator to promote proliferation, differentiation, and survival. 48 However, G-CSF along with GM-CSF can also act as proto-oncogenes, in which they are highly expressed in various tumors 49 - 51 and also frequently found in invasive breast cancer cells. 52 They were also found in abundance in the cytokine profile of metastatic 4T1 tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Ravoori et al cFms (25), and fibroblast growth factor receptor (26,27) are not noted to be essential drivers of ovarian cancer cells. Platelet-derived growth factor receptor-a inhibition does not inhibit SKOV3 cell proliferation (28).…”
Section: Experimental Studies: Ovarian Tumor Response To Tyrosine Kinmentioning
confidence: 95%
“…Anlotinib is a novel oral multi-targeted receptor tyrosine kinase inhibitor (TKI), which can effectively inhibit VEGFR, PDGFR, FGFR, C-KIT and other kinases, and has anti-tumor angiogenesis and anti-tumor growth effects [ 5 8 ]. Results from a number of previous phase II and III clinical trials have shown that amlotinib exhibits good antitumor activity in a variety of solid tumors, including non-small-cell lung cancer, renal carcinoma, gastric cancer, hepatocarcinoma and soft tissue sarcoma [ 9 ].…”
Section: Introductionmentioning
confidence: 99%